Polityka podatkowa państwa a rozwój mieszkalnictwa - Nowakowski, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
After Polish accession to the European Union in 2004, the VAT tax rate for most construction materials increased from the preferential rate of 7% to the basic rate of 22%. The legislator, aware of excessive fiscal burden to the taxpayer, introduced into the legal system the Act of 29 August 2005 on the refund for individuals of certain expenses related to housing construction. The Act was in force between 2006–2013, and was then replaced by the Act of 27 September 2013 on state aid in the purchase of afirst home for young people. The article presents an attempt to determine the effect of the law on VAT refund on the development of housing in 2006–2013, and also an attempt to assess the tax policy of the state in the field of housing. Furthermore, the article may give rise to a discussion of the merits of abandoning the institution of VAT refund for building materials.
Keywords: tax policy; tax effectiveness; tax preferences; VAT refund; housing development